Kevin Shaw interviewed by Rob Willis in Rob and Olya Willis folklore collection - Shaw, Kevin, 1951-; Willis, Rob, 1944-; Willis, Olya. (2004)
Folkloric recording.
Kevin Shaw recounts stories of his time in the Kimberley region and talks about his work.
Recorded by Olya Willis.
Recorded on Oct. 17, 2004 at Derby, W.A.
Digital master available
Kevin Shaw, born in 1951, has an interest in the Indigenous culture of the Kimberley region of Western Australia. He has worked as an Aboriginal Heritage Officer in the region. A noted photographer, he has published a book of images 'Mates'.
Timed summary (6 p.)
Keywords: Shaw, Kevin, -- 1951- -- Interviews; Photographers -- Western Australia -- Kimberley -- Interviews; Aboriginal Australians -- Western Australia -- Kimberley -- Social life and customs; Cultural property -- Protection -- Western Australia -- Kimberley; Photographers